Peran masyarakat adat dalam pelestarian hutan bambu di Dusun Busu Desa Slamparejo Kecamatan Jabung Kabupaten Malang - Putri, Evi Saskia; Wardhana, Hisyam Ismoe (Maliki Interdisciplinary Journal, 2024)
This research explores the role of indigenous communities in the conservation efforts of bamboo forests in Busu , Slamparejo, Jabung, Malang Regency. Through a qualitative approach, the study focuses on data collection through interviews, observations, and document analysis to understand the practices, values, and knowledge of indigenous communities related to bamboo forests. The research findings indicate that the indigenous community in Busu plays a key role in maintaining the sustainability of bamboo forests. They have a traditional management system that includes norms passed down through generations. The active involvement of the indigenous community in natural resource management involves participation in reforestation, regulation of logging, and supervision of activities that may harm the bamboo forest ecosystem. Furthermore, the study identifies local wisdom values that serve as the basis for conservation policies. The involvement of the indigenous community strengthens the understanding of ecology and culture closely related to bamboo forests. This creates a harmonious relationship between humans and the environment, playing a crucial role in the preservation of biodiversity and the sustainability of natural resources. This research contributes to understanding the dynamics of bamboo forest conservation by indigenous communities in this region, with implications for the development of policies that involve local communities in natural resource conservation efforts.